Human microRNA hsa‐miR‐1231 suppresses hepatitis B virus replication by targeting core mRNA. Issue 9 (16th May 2014) - Kohno, T.; Tsuge, M.; Murakami, E.; Hiraga, N.; Abe, H.; Miki, D.; Imamura, M.; Ochi, H.; Hayes, C. N.; Chayama, K.
Summary Pathogen‐specific miRNA profiles might reveal potential new avenues for therapy. To identify miRNAs directly associated with hepatitis B virus (HBV) in hepatocytes, we performed a miRNA array analysis using urokinase‐type plasminogen activator (uPA)–severe combined immunodeficiency (SCID) mice where the livers were highly repopulated with human hepatocytes and human immune cells are absent. Mice were inoculated with HBV‐infected patient serum samples. Eight weeks after HBV infection, human hepatocytes were collected from liver tissues, and miRNAs were analysed using the Toray 3D array system. The effect of miRNAs on HBV replication was analysed using HBV‐transfected HepG2 cells. Four miRNAs, hsa‐miR‐486‐3p, hsa‐miR‐1908, hsa‐miR‐675 and hsa‐miR‐1231 were upregulated in mouse and human livers with HBV infection. These miRNAs were associated with immune response pathways such as inflammation mediated by chemokine and cytokine signalling. Of these miRNAs, hsa‐miR‐1231, which showed high homology with HBV core and HBx sequences, was most highly upregulated. In HBV‐transfected HepG2 cells, overexpression of hsa‐miR‐1231 resulted in suppression of HBV replication with HBV core reduction. In conclusion, a novel interaction between hsa‐miR‐1231 and HBV replication was identified. This interaction might be useful in developing new therapeutic strategies against HBV.